1972
DOI: 10.1021/ed049p21
|View full text |Cite
|
Sign up to set email alerts
|

The oxides of nitrogen and their detection in automotive exhaust

Abstract: The Oxides of Nitrogen and their It is assumed that nitrogen and small amounts of inert gases

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
1
0

Year Published

1976
1976
2003
2003

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 14 publications
1
1
0
Order By: Relevance
“…Because Au oxide forms at more cathodic potentials in base 45 than in acid and it has been reported that the onset of NO 2 reduction is similarly pH dependent, 46 a similar explanation of the mechanism of NO x oxidations on this basis is reasonable. The NO 2 oxidation apparently starts to occur at ͓Ϫ50 mV͔ before NO oxidation ͓at ϩ100 mV͔, and this is consistent with the NO 2 being a stronger acid and forming a HONO, NO 2 Ϫ , or other species with water which can easily be oxidized to NO 3 or NO 3 Ϫ . The reactions available to NO and the reaction of NO with oxygen to form NO 2 appear to be much slower than the reactions of NO 2 with water at the electrode surface.…”
Section: ͓No͑g͒] ͓No͑aq͒] ͓5͔supporting
confidence: 69%
See 1 more Smart Citation
“…Because Au oxide forms at more cathodic potentials in base 45 than in acid and it has been reported that the onset of NO 2 reduction is similarly pH dependent, 46 a similar explanation of the mechanism of NO x oxidations on this basis is reasonable. The NO 2 oxidation apparently starts to occur at ͓Ϫ50 mV͔ before NO oxidation ͓at ϩ100 mV͔, and this is consistent with the NO 2 being a stronger acid and forming a HONO, NO 2 Ϫ , or other species with water which can easily be oxidized to NO 3 or NO 3 Ϫ . The reactions available to NO and the reaction of NO with oxygen to form NO 2 appear to be much slower than the reactions of NO 2 with water at the electrode surface.…”
Section: ͓No͑g͒] ͓No͑aq͒] ͓5͔supporting
confidence: 69%
“…2 NO is formed in processes of combustion and found in effluents from coal-fired power plants and automobiles. 3,4 NO 2 can also cause adverse health effects 5 and causes environmental impact when reacting with water vapor in the atmosphere to contribute to acid rain. Therefore, sensitive and selective detection methods for these gases are required.…”
mentioning
confidence: 99%